Comparative Analysis of E-commerce for Student Shopping Optimization Using the SAW and SMART Methods - Rifqi Mahdhika Rindani; Yaslinda Lizar (International journal of technology and education research, 2026)
The growth of e-commerce platforms in Indonesia encourages students to actively shop online. However, the large number of platform choices makes it difficult to determine which one is most optimal according to students' needs and budget constraints. This study aims to analyze and compare five e-commerce platforms, namely Shopee, TikTok Shop, Tokopedia, Lazada, and Blibli, using two multi-criteria decision-making methods, namely Simple Additive Weighting (SAW) and Simple Multi-Attribute Rating Technique (SMART). This type of research is a comparative descriptive quantitative study with a population of active student e-commerce users. Data were collected through a questionnaire survey to 11 active student respondents with eight assessment criteria including product price, promo/discount, free shipping, delivery speed, ease of use of the application, product completeness, transaction security, and service quality. The results of the SAW calculation show that Shopee obtained the highest score of 0.9744, followed by TikTok Shop (0.9656), Tokopedia (0.8455), Blibli (0.7964), and Lazada (0.7331). The SMART method produced a ranking identical to Shopee's utility value of 0.8962. The Spearman correlation between the two methods reached rs = 1.0000, indicating perfect consistency of results. These findings confirm that Shopee is the most optimal platform for college students, followed by TikTok Shop as a competitive alternative.